The influence of upper-body mechanics, anthropometry and isokinetic strength on performance in wrist-spin cricket bowling. Issue 3 (1st February 2020) - Spratford, Wayne; Elliott, Bruce; Portus, Marc; Brown, Nicholas; Alderson, Jacqueline
ABSTRACT: Delivering a cricket ball with a wrist-spin (WS) bowling technique is considered one of the game's most difficult skills. Limited biomechanical information exists for WS bowlers across skill levels. The purpose of this study was to compare biomechanical, isokinetic strength and anthropometric measures between elite (12) and pathway bowlers (eight). Data were collected using a motion analysis system, dynamometer and a level-two anthropometrist. A regression analysis identified that performance was best explained by increased wrist radial deviation torque and longitudinal axis rotational moments at the shoulder and wrist. From back foot impact (BFI) to ball release (BR), elite bowlers rotated their trunks less, experienced less trunk deceleration resulting in a more front-on position and increased pelvis rotation angular velocity. They also displayed an increased shoulder internal rotation moment as the upper arm moved from external into internal rotation and was a major contributor in the subsequent differences observed in the distal segments of the bowling limb. Anthropometric differences were observed at the wrist and finger joints and may be used to form the basis for talent identification programmes. This study highlights the important contribution to bowling performance of the musculature responsible for producing long axis rotations of the bowling limb.